Measuring adolescents’ social goals during lower secondary school - Hanna-Riitta Ståhl; Niina Junttila; Päivi M. Niemi (Pabst Science Publishers, 2022)
The purpose of this study was to investigate Finnish adolescents’ (n = 390) social goals during three years of lower secondary school at six (6) time points (from age 12 to age 16). We intended to study the measurement validity and longitudinal stability of adolescents’ social goals as measured by the Interpersonal Goals Inventory for Children (IGI-C), developed by Ojanen, Grönroos and Salmivalli (2005). The interpersonal circumplex model is based on two pairs of factors: (1) agency and submission and (2) communion and separation. We aimed to test whether the phenomena of social goals could be captured as individual factors using these four qualities instead of the standard two broader dimensions; Agentic and Communal. These dimensions are usually divided into eight sub-scales according to different combinations. This hypothesized four-factor model was modeled and confirmed using longitudinal confirmatory factor analysis (LCFA). According to the LCFA, the stability within each factor was at least moderate, and the interrelations between the factors varied over time. Acceptable concurrent and discriminant validity was shown by mostly stronger correlations within the social goal sum scores than between the social goals and social anxiety scores. Compared to the original IGI-C measurement tool, the tool utilized in this study, the Scale of Interpersonal Goals for Adolescents (SIG-A), provides a more simplified measurement. This simplified measurement offers a new way to examine adolescents’ social goals in terms of four separate factors. Moreover, with this measurement tool, it is possible to study the social development of adolescents in a more detailed manner - one social goal at a time.